Primary School Strategies in Optimising Self-Reflection Activities in Merdeka Curriculum - Kiki Fatmawati (Universitas Islam Lamongan, 2024)
Merdeka Curriculum emphasises student-centred learning, providing flexibility to adapt the curriculum to local needs and student characteristics. One important component of this approach is the integration of self-reflection activities. However, the implementation of self-reflection in the Merdeka Curriculum at the primary level still faces various challenges. Not all schools are able to optimise self-reflection activities effectively and integrated in the daily learning process. this study aims to explore the strategies used by elementary schools in optimising self-reflection activities in the Merdeka Curriculum. In this study, researchers used a qualitative method using several data collection techniques, namely observation, interviews and documentation. The data sources in this study focused on principals and teachers. The data analysis technique uses Miles and Huberman. The findings of this study are the strategies carried out from the aspect of teacher self-reflection in the form of questions contained in the form of experience notes, self-reports, autobiographies, journals, diaries, peer reflection in the form of discussing, observing and reflecting on the learning process, reflection by the principal in the form of holding discussions, providing trigger questions and observations to directly observe the learning process and reflection by students by giving questionnaires and direct questions.